Effects of Value Clarification and Action Learning Instructional Strategies on School Children’s Attitude to Civic Education Concepts: The Mountain Learning Ecologies Experience - Ige, Olugbenga Adedayo (Pedagogika, 2018)
The current study determined the effectiveness of value clarification and action learning teaching modes on school-age children’s attitude to civic education concepts. It also determined the moderating effects of gender and academic ability on school-age children’s attitude to civic education concepts. In a randomized pre-post-design, 29 school-age children were in learning ecology I (experimental group I), 24 were in learning ecology II (experimental group II), while 93 were in learning ecology III (the control group). There was a significant effect of treatment on school-age children’s attitude to civic education concepts. Further research is proposed to study the sustainability of observed effects in mountain learning ecologies.